Information and Analytical Support of Diagnostics and Monitoring of Social Infrastructure: Global and National Challenges - Komelina, Ðžlha; Lyakhov, Aleksandr; Fursova, Natalia (International Journal of Engineering and Technology, 2018)
In this article proposes the development of information and analytical support of diagnostics and monitoring of social infrastructure in the context of global and national challenges. Economic and statistical analysis of indicators of innovative activity of enterprises in Ukraine was conducted, low innovative activity of enterprises was revealed in the current market situation. In order to increase innovation development in Ukraine, scientific and methodological approaches were developed for the development of organizational principles for diagnostics and monitoring of the status of social infrastructure objects. The stages of information and analytical support of diagnostics and monitoring of social infrastructure, evaluation criteria are proposed. The basic requirements for information and analytical support and functional requirements are summarized and systematized.The mathematical approach for processing indicators of the activities of social infrastructure organizations has been developed in order to determine their rating positions according to modern criteria of activity evaluation. This scientific approach will enhance the ability to overcome the state monopoly in the provision of social services and distribution of orders in Ukraine, will provide the opportunity for wide involvement of public, charitable, religious organizations and local initiatives in the provision of social services.
Keywords: diagnostics; information and analytical support; monitoring; social infrastructure.